2015
DOI: 10.1186/s13567-015-0210-3
|View full text |Cite
|
Sign up to set email alerts
|

Maternal immunity enhances systemic recall immune responses upon oral immunization of piglets with F4 fimbriae

Abstract: F4 enterotoxigenic Escherichia coli (ETEC) cause diarrhoea and mortality in piglets leading to severe economic losses. Oral immunization of piglets with F4 fimbriae induces a protective intestinal immune response evidenced by an F4-specific serum and intestinal IgA response. However, successful oral immunization of pigs with F4 fimbriae in the presence of maternal immunity has not been demonstrated yet. In the present study we aimed to evaluate the effect of maternal immunity on the induction of a systemic imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Therefore, E. coli F4 vaccination might be one of the alternative strategies once ZnO is banned in the EU by 2022. Besides vaccination, several other alternative strategies, such as adapted nutritional strategies (feed consistency, lower crude protein, digestible fibers and other dietary fibers), prebiotics, probiotics, organic acids, MCFAs, specific IgA antibodies and oral vaccination have been explored [19][20][21][22][23][24][25][26][27][28][29]33,34,[38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, E. coli F4 vaccination might be one of the alternative strategies once ZnO is banned in the EU by 2022. Besides vaccination, several other alternative strategies, such as adapted nutritional strategies (feed consistency, lower crude protein, digestible fibers and other dietary fibers), prebiotics, probiotics, organic acids, MCFAs, specific IgA antibodies and oral vaccination have been explored [19][20][21][22][23][24][25][26][27][28][29]33,34,[38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to piglet screening for pathogen susceptibility, the pathogen-specific immunization of piglets and sows should be evaluated. In fact, beyond the passive immunity derived from sow’s milk which can affect the piglet’s responsiveness to ETEC immediately after weaning, it has been shown that maternal immunity can persist in piglet blood and can induce a systemic immune response in the piglets [83], resulting in a less efficient piglet response to the ETEC challenge. Therefore, in studies where feeding strategies with the aim of contracting the ETEC infection, selecting piglets from sows not specifically immunized for ETEC and not infected with the pathogen previously has been recommended.…”
Section: Setting Of the Challenge Modelmentioning
confidence: 99%
“…Therefore, in studies where feeding strategies with the aim of contracting the ETEC infection, selecting piglets from sows not specifically immunized for ETEC and not infected with the pathogen previously has been recommended. For studies where vaccine strategies are tested, the passage of maternal immunization should be considered for a correct interpretation of the results, as suggested by Nguyen et al [83].…”
Section: Setting Of the Challenge Modelmentioning
confidence: 99%
“…Therefore, alternative approaches to control PWD due to pathogenic E. coli should be explored. Several alternative strategies, such as adapted nutritional strategies (feed consistency, lower crude protein, digestible fibers and other dietary fibers), prebiotics, probiotics, organic acids, MCFAs, specific IgA antibodies and oral vaccination have been explored [19][20][21][22][23][24][25][26][27][28][29]33,34,[37][38][39][40]].…”
Section: Discussionmentioning
confidence: 99%